If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 + -6x = 10x + 19 Reorder the terms: 115 + -6x = 19 + 10x Solving 115 + -6x = 19 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 115 + -6x + -10x = 19 + 10x + -10x Combine like terms: -6x + -10x = -16x 115 + -16x = 19 + 10x + -10x Combine like terms: 10x + -10x = 0 115 + -16x = 19 + 0 115 + -16x = 19 Add '-115' to each side of the equation. 115 + -115 + -16x = 19 + -115 Combine like terms: 115 + -115 = 0 0 + -16x = 19 + -115 -16x = 19 + -115 Combine like terms: 19 + -115 = -96 -16x = -96 Divide each side by '-16'. x = 6 Simplifying x = 6
| 2n-7=45 | | =2x-x^2 | | n/4-8=10 | | 4x-4=11x-81 | | x-2=2x-men | | 60-3x=6x+21 | | 7x+14=10x+5 | | 2x-10=-2+18 | | 5x+8=53 | | 5x+40=60 | | (x+3)=x+10 | | 2n+9=-29 | | 2x+20=8x+2 | | 10x^2-3c-27= | | 5x+18=13x-62 | | 16x^2-41x+25=0 | | 2x=9x-28 | | 12+b/6=16 | | 5a+6=41 | | -6k^2-13k-6= | | 2(4x+2)=28 | | 2x-16=3(2x+2)-2 | | -3x+20=8 | | 64-5x=3x+14 | | -2x+15=3x-40 | | 6x=8x-4 | | 3+4n=15 | | 3x=36-6x | | -2h^2+5h+3= | | -8x+4=2 | | 5y-7=-3 | | (8+5)n=53 |